Serum hepatitis B core‐related antigen level stratifies risk of disease progression in chronic hepatitis B patients with intermediate viral load - Tseng, Tai‐Chung; Liu, Chun‐Jen; Yang, Wan‐Ting; Hsu, Chen‐Yang; Hong, Chun‐Ming; Su, Tung‐Hung; Tsai, Cheng‐Hsueh; Chen, Chi‐Ling; Yang, Hung‐Chih; Liu, Chen‐Hua; Chen, Hsiu‐Hsi; Chen, Pei‐Jer; et al. (Alimentary pharmacology & therapeutics, 2021)
Summary Background Patients with chronic hepatitis B virus (HBV) infection are at risk of developing liver disease. Serum hepatitis B core‐related antigen (HBcrAg) is a new biomarker for intrahepatic templates for HBV replication. Aim To explore whether a high HBcrAg level is associated with increased risk of cirrhosis, especially in patients with intermediate viral load (HBV DNA 2000‐19 999 IU/mL) due to their moderate risk of disease progression. Methods A total of 1673 treatment‐naïve, non‐cirrhotic patients with negative hepatitis B e antigen (HBeAg) and alanine aminotransferase (ALT) level <40 U/L at baseline were enrolled. We explored the relationship between baseline levels of HBcrAg and cirrhosis development in all patients, and whether a higher HBcrAg level (<10 vs ≥10 KU/mL) was associated with an increased risk of disease progression in those with intermediate viral load. Results Of the 1673 patients, 104 developed cirrhosis after a mean follow‐up of 15.9 years. Higher HBcrAg levels were associated with increased incidence of cirrhosis, cirrhosis‐related complications, and liver‐related death. In 445 patients with intermediate viral load, the cirrhosis risk stratified by HBcrAg level of 10 KU/mL yielded a hazard ratio of 3.22 (95% CI: 1.61‐6.47). The risk stratification remained significant when exploring other pre‐cirrhosis endpoints, including HBeAg‐negative hepatitis, hepatitis flare, and HBV DNA >20 000 IU/mL after 3 years of follow‐up. Conclusions In HBeAg‐negative patients with normal ALT levels, higher HBcrAg levels are associated with increased risk of cirrhosis. Among those with intermediate viral load, HBcrAg <10 KU/mL defines a low‐risk group for disease progression.